Knowledge Of Breast Cancer Prevention And 'Cerdik' Behavior In Adult Women In Tlogomas Malang - Ronasari Mahaji Putri; Wahidyanti Rahayu Hastutiningtyas (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
The incidence of breast cancer continues to rise and constitutes a significant global health issue, including in Indonesia. Early detection of breast cancer, although seemingly simple, is often neglected by women. This study aims to assess knowledge regarding breast cancer prevention and its correlation with the â€œCERDIKâ€ behavior among adults. The research design is non-experimental with a cross-sectional approach. The population comprises all adults in the Tlogomas area, with a sample of 81 individuals selected through accidental sampling. The independent variable is knowledge of breast cancer prevention, while the dependent variable is the "CERDIK" behavior. The instrument used was a questionnaire, which had undergone validity and reliability testing by the researchers. Data analysis was performed using the Fisher exact test. The results indicate that nearly all respondents (86.2%) possess insufficient knowledge of breast cancer prevention; the majority (55.6%) exhibit moderate "CERDIK" behavior, and there is no significant correlation between knowledge of breast cancer prevention and the "CERDIK" behavior among adults in Tlogomas (p-value 0.511). It is recommended that future research conduct health promotion activities regarding breast cancer prevention and examine attitudes and determinant factors related to the "CERDIK" behavior.